Ecology of meromictic lakes - Gulati, R. D.; Zadereev, Egor S.; Degermendzhi, Andrei Georgievich (Springer, 2017)
This volume presents recent advances in the research on meromictic lakes and a state-of-the art overview of this area. After an introduction to the terminology and geographic distribution of meromictic lakes, three concise chapters describe their physical, chemical and biological features. The following eight chapters present case studies of more than a dozen meromictic lakes, showing the variety of physical and biochemical processes that promote meromixis. The result is a broad picture of the ecology and biochemistry of meromictic lakes in tropical and cold regions, in man-made pit lakes and euxinic marine lakes, and in freshwater as well as hypersaline lakes. In the final chapter the editors provide a synthesis of the topic and conclude that the study of meromictic lakes also offers new insights into the limnology of inland lakes. The book appeals to researchers in the fields of ecology, limnology, environmental physics and biophysics.
Keywords: Lake ecology.; Lake acidification.; elektronické knihy; electronic books